$T=K(\theta \cdot p +T_0)$
- $32.4=K(2\theta +25)\qquad \to (1)$
- $42.0=K(5\theta +30)\qquad \to (2)$
Divide the equation $(1)$ by equation $(2),$ and we get
$\dfrac{32.4}{42.0}=\dfrac{K(2\theta +25)}{K(5\theta +30)}$
$\implies\dfrac{324}{420}=\dfrac{2\theta +25}{5\theta +30}$
$\implies\dfrac{27}{35}=\dfrac{2\theta +25}{5\theta +30}$
$\implies 27(5\theta +30)=35(2\theta +25)$
$\implies 135\theta +810=70 \theta +875$
$\implies 135\theta -70 \theta =875-810$
$\implies 65\theta = 65$
$\implies \theta = 1$
So, correct answer is $(B).$